2010
DOI: 10.1287/mnsc.1100.1157
|View full text |Cite
|
Sign up to set email alerts
|

Impossible Frontiers

Abstract: A key result of the Capital Asset Pricing Model (CAPM) is that the market portfoliothe portfolio of all assets in which each asset's weight is proportional to its total market capitalization-lies on the mean-variance-efficient frontier, the set of portfolios having mean-variance characteristics that cannot be improved upon. Therefore, the CAPM cannot be consistent with efficient frontiers for which every frontier portfolio has at least one negative weight or short position. We call such efficient frontiers "im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…4 Numerous papers have found that various long-only market indexes are not mean-variance efficient portfolios (e.g., see Gibbons et al (1989); Gibbons (1982); Jobson and Korkie (1982); Kandel (1984); Shanken (1985Shanken ( , 1986; Kandel andStambaugh (1987a, 1987b); Gibbons et al (1989); Haugen and Baker (1991); MacKinlay and Richardson (1991); Zhou (1993); Brière et al (2013), and others). According to Brennan and Lo (2010), it is virtually impossible for long-only market indexes to be efficient portfolios. Supporting this proposition, many studies have found that short positions are needed to achieve efficiency (e.g., see Pulley (1981); Levy (1983); Kallberg and Ziemba (1983); Kroll et al (1984); Green and Hollifield (1992); Jagannathan and Ma (2003); Brennan and Lo (2010); Levy and Ritov (2010), and others).…”
Section: Conflicts Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Numerous papers have found that various long-only market indexes are not mean-variance efficient portfolios (e.g., see Gibbons et al (1989); Gibbons (1982); Jobson and Korkie (1982); Kandel (1984); Shanken (1985Shanken ( , 1986; Kandel andStambaugh (1987a, 1987b); Gibbons et al (1989); Haugen and Baker (1991); MacKinlay and Richardson (1991); Zhou (1993); Brière et al (2013), and others). According to Brennan and Lo (2010), it is virtually impossible for long-only market indexes to be efficient portfolios. Supporting this proposition, many studies have found that short positions are needed to achieve efficiency (e.g., see Pulley (1981); Levy (1983); Kallberg and Ziemba (1983); Kroll et al (1984); Green and Hollifield (1992); Jagannathan and Ma (2003); Brennan and Lo (2010); Levy and Ritov (2010), and others).…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…According to Brennan and Lo (2010), it is virtually impossible for long-only market indexes to be efficient portfolios. Supporting this proposition, many studies have found that short positions are needed to achieve efficiency (e.g., see Pulley (1981); Levy (1983); Kallberg and Ziemba (1983); Kroll et al (1984); Green and Hollifield (1992); Jagannathan and Ma (2003); Brennan and Lo (2010); Levy and Ritov (2010), and others). More generally, Kothari et al (1995) have argued that the equity portfolio most highly correlated with the market portfolio is efficient.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Factor contributions are 308 basis points, led by medium‐term momentum factor contributions of 148 basis points ( t = 8.06). The authors recently used the Boolean signal argument to address a footnote in Brennan and Lo (), which repeated several Wall Street “researchers” claiming that Markowitz MV analysis can produce impossible frontiers. We do not find such results with a reasonably specified upper stock bound and reasonable turnover constraints.…”
Section: The Existence and Persistence Of Financial Anomalies: 2003–2018mentioning
confidence: 99%